Merkel Cell Carcinoma and Diagnostic Experience in a Reference Hospital: A Case Series. (19th February 2020) - López Panqueva, Rocio del Pilar; Suarez-Zamora, David A.; Barrera-Herrera, Luis E.; Rolón Cadena, Mariam
Abstract : Merkel cell carcinoma (MCC) is a rare poorly differentiated neuroendocrine tumor, usually located in sun-exposed skin, with aggressive behavior and with high recurrence risk and metastatic disease. In Latin America, case series have been published, and it does not exceed 32 patients in 10 years, and in Colombia, there are case reports. We present a descriptive retrospective cross-sectional study in patients diagnosed with MCC in the Department of Pathology and Laboratories at the University Hospital Fundación Santa Fe de Bogotá(FSFB) between January 2003 and December 2018. We present the demographic, clinical, and pathological variables of these patients, as well as a literature review.